(untitled) (World Bulletin of Public Health, 2023)
Tennis is one of the most effective means of maintaining vitality and improving health. In addition to physical activity, it also gives a great emotional charge, creates a good mood and gives a sense of satisfaction with one’s activity, which is no less important than physical activity.